Learning Achievements of Muhammadiyah Cadres in Higher Education During Covid 19: Prestasi Belajar Kader Muhammadiyah Lingkup Perguruan Tinggi Di Era Covid 19 - Nurmitasari, Nurmitasari; Astuti, Robia; Khasanah, Binti Anisaul (Universitas Muhammadiyah Sidoarjo, 2021)
The responses given by final year FKIP UMPRI Lampung students to Muhammadiyah were different even though the treatment given was the same in the regeneration process. Whereas experience in the organization as a cadre is very important in dealing with pandemic conditions, so that it affects student learning achievement. This is the background of this research which aims to reveal the learning achievements of Muhammadiyah cadres within the scope of universities in the era of covid-19 so that it can be a consideration for Muhammadiyah universities to further strengthen Muhammadiyah cadres and prospective Muhammadiyah cadres through better regeneration programs. This type of research is a comparative quantitative study with a population of all final year students of FKIP UMPRI, amounting to 268. The sample in this study was 20% of the population using a proportional cluster random sampling technique of 54 students. The use of data analysis techniques in this study is a t-test with test prerequisites, namely normality test and homogeneity test. Based on data analysis, it was found that there was no difference in learning achievement between Muhammadiyah cadres and non-Muhammadiyah cadres in the scope of universities in the covid-19 era.